Helicobacter pylori antibiotic resistance profile in Chinese children with upper gastrointestinal symptoms and a literature review for developing personalized eradicating strategies - Zhou, Danli; Wang, Wuyu; Gu, Lan; Han, Meiling; Hao, Wujuan; Huang, Junfeng; Lin, Qiong; Wang, Yan (Frontiers in Pharmacology, 2024)
Background: Helicobacter pylori (H. pylori) infections typically occur in early childhood. Although the prevalence of H. pylori in children is lower than that in adults, the eradication rate of this infection in children is relatively low because of resistance. In this study, we analyzed personalized treatment strategies to achieve treatment goals based on H. pylori resistance characteristics. This retrospective single-center study was conducted between January 2019 and December 2022 and enrolled 1587 children who presented with upper gastrointestinal symptoms and underwent endoscopy. H. pylori culturing and antimicrobial susceptibility testing were performed. Results: Culture-positive results for H. pylori were obtained in 535 children. The resistance rates to clarithromycin (CLA), metronidazole (MET), and levofloxacin (LEV) were 39.8%, 78.1%, and 20.2%, respectively. None of the isolates were resistant to tetracycline (TET), amoxicillin (AMO), or furazolidone (FZD). Double resistance rates to CLA+MET, CLA+LEV, and MET+LEV were 19.1%, 3.0%, and 5.8%, respectively. Notably, triple-resistant to CLA+MET+LEV was 9.7%. Based on susceptibility tests, individualized triple therapy [proton pump inhibitor (PPI) +AMO+CLA/MET] was selected for 380 children with H. pylori sensitive to MET and/or CLA. In 155 children resistant to CLA and MET, bismuth-based quadruple therapy was recommended; for unable to receive bismuth, concomitant therapy was recommended for 14 children (<8 years of age); triple therapy with TET was recommended for 141 children (>8 years of age), with 43 children (>14 years of age) requiring FZD rather than TET. Conclusions: Resistance to H. pylori in Chinese children was relatively poor. Personalized therapy regimens should be based on susceptibility tests and avoided factors associated with treatment failure.